THE EFFECT OF COMPENSATION, WORK MOTIVATION, AND WORK ENVIRONMENT ON EMPLOYEE MORALE AT CV. CENING BAGUS GIANYAR - Ni Kadek Dina Pratiwi; Ni Made Dwi Puspitawati; Tiara Carina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
Work morale reflects the condition of employees in their work environment. If work morale is good, the company will gain profits in accordance with company goals. In order to realize high work morale in employees, optimal attention is needed to compensation, work motivation and pay attention to the employee's work environment. This study aims to determine the effect of compensation, work motivation and work environment on employee work morale at CV. Cening Bagus Gianyar. The number of samples used was 59 people who are employees of CV. Cening Bagus Gianyar. The sampling technique used in this study was the census method or saturated sample. Data collection was carried out through documentation, interviews and questionnaires. The data analysis technique used in this study was multiple linear regression analysis processed using SPSS software version 25.00 for Windows. Based on the results of the analysis, this study shows that compensation, work motivation and work environment each have a positive and significant effect on work morale at CV. Cening Bagus Gianyar. This means that the increasing and the work environment have a positive and significant effect on employee work morale at CV. Cening Bagus Gianyar.